Model Validation and Uncertainty Quantification, Volume 3 Proceedings of the 34th IMAC, A Conference and Exposition on Structural Dynamics 2016 - Atamturktur, Sez; Schoenherr, Tyler; Moaveni, Babak; Papadimitriou, Costas (Conference Proceedings of the Society for Experimental Mechanics Series,, 2016)
Model Validation and Uncertainty Quantifi cation, Volume 3. Proceedings of the 34th IMAC, A Conference and Exposition on Dynamics of Multiphysical Systems: From Active Materials to Vibroacoustics, 2016, the third volume of ten from the Conference brings together contributions to this important area of research and engineering. Th e collection presents early findings and case studies on fundamental and applied aspects of Structural Dynamics, including papers on: • Uncertainty Quantifi cation & Model Validation • Uncertainty Propagation in Structural Dynamics • Bayesian & Markov Chain Monte Carlo Methods • Practical Applications of MVUQ • Advances in MVUQ & Model Updating • Robustness in Design & Validation • Verifi cation & Validation Methods.